Future anxiety during the switch to distance learning during the Coronavirus (COVID-19) pandemic and its relationship to some variables among secondary school students in Madinah - Al-Harbi, Enas Murdhi Naji (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of future anxiety in light of the shift to distance education during COVID-19 among secondary school students in Al Madinah Al Munawwarah and to identify the differences in the degree of future anxiety due to some demographic variables (gender - major- income level). The study sample included (403) female and male secondary school students in Al Madinah Al Munawwarah, in the second and third secondary grades, who were chosen by the simple random sampling. In order to achieve the objectives of the study, the researcher adopted the Analytical descriptive approach. The researcher used the Future Anxiety Scale prepared by (Shuqair, 2005). The study concluded that there was simple future anxiety in light of the shift to distance education during COVID-19 among second and third secondary school students in Al Madinah Al Munawwarah, and there were no statistically significant differences at (0.05) level in the degree of future anxiety in light of the shift to distance education during COVID-19 due to demographic variables (gender, major, income level) variable among the second and third secondary school students in Al Madinah Al Munawwarah. In light of the above-mentioned results, the researcher recommends that Ministry of Education at Saudi Arabia has to continue implementing the distant education, as the results of the current study showed that it does not, significantly, affect future anxiety levels among high school students.